COVID-19 VACCINE ACCEPTANCE AMONG PUBLIC HEALTH STUDENTS IN GRESIK CITY - Nihayatul Munaa; Ida Herwati Hafid; Lailatul Kodriyah (UNUSA Press, 2021)
One of the programs that can protect the community from COVID-19 is vaccination. Vaccination is an effective approach to prevent infection and reduce mortality. This study was conducted to determine the perception of acceptance of the Covid-19 vaccine among public health students as potential health workers in the future. This is a mixed-method study with 140 respondents of public health students. The data were analyzed using a non-parametric binomial test. The results of this study Statistics prove that as prospective health workers, the public health student has a good level of acceptance of the COVID-19 vaccine (p-value 0.002). However, several indicators still make students doubt the COVID-19 vaccine, including the effectiveness of the vaccine (p-value 0.006), information circulating (p-value 0,041), and the mandate from the government (p-value 0,041). Conclusion this research is the government must provide information on the effectiveness of the vaccine to the entire community so that the COVID-19 vaccine can be accepted by the public health worker to be and the public community.